2015
DOI: 10.1111/andr.12033
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic visualization of intravasal spermatozoa is positively associated with patency after bilateral microsurgical vasovasostomy

Abstract: SUMMARYWe evaluated pre-operative and intraoperative factors associated with successful patency following bilateral microsurgical vasovasostomy (VV). We retrospectively reviewed the charts of 1331 men who underwent bilateral VV by two surgeons between 2006 and 2013. Vasal fluid was examined intraoperatively for gross quality (i.e., clear or opaque and creamy/thick) and for the presence of spermatozoa on microscopy (i.e., whole spermatozoa, sperm fragments, or azoospermia). Post-operative patency was assessed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…In a systematic review and meta‐analysis of the reports on the association between the presence of sperm in the intraoperative vasal fluid and patency, it was reported that the odds ratio of postoperative patency was 4.1‐fold higher in the presence of intravasal sperm or sperm parts than in their absence . Another study confirmed the association between the presence of intravasal spermatozoa during a VV and having a successful patency outcome in a large series from 2 experienced surgeons (n = 1331) . It also showed that the odds of postoperative patency were ~14‐fold higher in the presence of intravasal whole spermatozoa than by having merely sperm fragments or azoospermia.…”
Section: Predictors Of Postoperative Patency and Pregnancymentioning
confidence: 86%
See 4 more Smart Citations
“…In a systematic review and meta‐analysis of the reports on the association between the presence of sperm in the intraoperative vasal fluid and patency, it was reported that the odds ratio of postoperative patency was 4.1‐fold higher in the presence of intravasal sperm or sperm parts than in their absence . Another study confirmed the association between the presence of intravasal spermatozoa during a VV and having a successful patency outcome in a large series from 2 experienced surgeons (n = 1331) . It also showed that the odds of postoperative patency were ~14‐fold higher in the presence of intravasal whole spermatozoa than by having merely sperm fragments or azoospermia.…”
Section: Predictors Of Postoperative Patency and Pregnancymentioning
confidence: 86%
“…It reported that a longer obstructive interval, an absence of a sperm granuloma on physical examination, and the presence of sperm or sperm parts at the time of reversal were associated with the success of a VR. The predictors of postoperative patency and pregnancy that have been reported in recent years are summarized in Table . With marked improvement in reproductive techniques, including microscopic epididymal sperm aspiration and TESE in combination with ICSI, the number of treatment options for couples who are challenged with male infertility has increased.…”
Section: Predictors Of Postoperative Patency and Pregnancymentioning
confidence: 99%
See 3 more Smart Citations